The Relationship of Antenatal Care Service Standards with the Incident of Anemia in Pregnant Women - Nurul Hidayati; Mahfuzhah Deswita Puteri (CV Media Inti Teknologi, 2024)
The aim of this research is to find out whether there is a relationship between Service Standards Antenatal Care With the incidence of anemia in pregnant women at the Astambul Community Health Center, Banjar Regency. Quantitative research method with cross-sectional. Number of populations and samples using techniques Total Sampling namely 50 respondents, data collection was carried out using observation sheets and register books with testsrank spearman. The results of the study showed that 30 pregnant women (60%) experienced anemia. There were 27 pregnant women whose pregnancy checks did not meet the ANC 10 T service standards (54%). Testrank spearmanThe p-value was 0.002<0.05 with a correlation coefficient of 0.426** which was positive. The conclusion of this research is that H0 is rejected, and Ha is accepted, meaning that there is a strong and significant relationship in the same direction between Service Standards. Antenatal Care with the incidence of anemia in pregnant women at the Astambul Community Health Center, Banjar Regency. Pregnant women must always check their pregnancy according to the time specified based on the midwife's recommendations and continue to take the Fe tablets that have been given by the midwife